2019
DOI: 10.1051/matecconf/201926504014
|View full text |Cite
|
Sign up to set email alerts
|

SWAT modeling of the soil properties in GIS-environment: initial calculations

Abstract: The problem of soil parameters modeling and input data preparation are considered in the article. The use of Soil and Water Assessment Tool was analyzed. The question of the soil water content and basic soil agronomic characteristics was considered. The SWAT project was created for the period of 2014-2017 years and could be prolonged. A soil map and cartographic information were digitized for the analysis of soil characteristics. An assessment of soils moisture absorption in different key areas was made in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…3). Similarly, a hydrographic network with the sub-basins can be calculated using the SWAT model (ArcSWAT2009) [24,25]. The results of modeling of relief effect on the distribution of moisture in the soil showed that height differences affect the amount of soil moisture across the profile (horizons 0-100 cm) for the study area.…”
Section: The Results Of Studies Of Relief Effect On Soil Moisture Bas...mentioning
confidence: 99%
“…3). Similarly, a hydrographic network with the sub-basins can be calculated using the SWAT model (ArcSWAT2009) [24,25]. The results of modeling of relief effect on the distribution of moisture in the soil showed that height differences affect the amount of soil moisture across the profile (horizons 0-100 cm) for the study area.…”
Section: The Results Of Studies Of Relief Effect On Soil Moisture Bas...mentioning
confidence: 99%